HISTORICAL AND CULTURAL VALUE OF FOLK MUSICAL PERFORMING ART (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article examines the current state of folk music perfomers, their perception and attitude of the younger generation towards it, and describes the negative influense of Western music on traditional music. The article also notes that one of the most important issues is the scientific study of folk music and determines the issues of preserving and depeloping the traditions of folk musical performance.
Keywords: of folk musical performance, musical heritage, tradition, folklore, ethnography, modern music, historical and cultural, academic performance, professional.